Galvanostatic and potentiostatic reduction of multilayer graphene oxide in alkaline electrolyte - Brudnik, Sergei Vital'evich; Yakovlev, Andrei Vasil'evich; Yakovleva, Elena Vladimirovna; Alferov, Andrei Alekseevich (Электрохимическая энергетика, 2025)
The results of the study of electrochemical reduction of multilayer graphene oxide in galvanostatic and potentiostatic modes are presented, the possibility of using the alkaline electrolyte KOH with the concentration of 0.01 M is shown. The identification of electrochemically reduced graphene oxide was carried out by XRD analysis, IR and Raman spectroscopy. Based on the analysis of Raman spectra, the increase in the total defectiveness,the decrease in the concentration of oxygen-containing groups and the decrease in the crystallite size of graphene oxide were determined.